The Actantial Model Analysis in The Film Rosaline (2022) - Azzahro Aghfa; Mardliya Pratiwi Zamruddin (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2026)
This research analyzes the conflicts in the film Rosaline using Greimas’ actantial model. Employing a qualitative method, it examines how actants, such as the sender, subject, object, helper, opponent, and receiver, interact to shape the narrative. The research applies Miles and Huberman’s three step content analysis method: data reduction, data display, and conclusion drawing. The researcher found thirty one data, which consist of four external conflicts and one internal conflict. The findings reveal that each conflict in Rosaline is structured by a distinct combination of actantial models. The results emphasize how shifting actant roles drive conflict progression and resolution, demonstrating the dynamic interaction between external obstacles and internal motivations in shaping narrative tension. By applying Greimas' actantial model, this research provides insights into how conflicts in the film Rosaline are resolved. The external and internal pressures shape the actions of the actants and influence the development and plot of the story.